2014
DOI: 10.2741/e692
|View full text |Cite
|
Sign up to set email alerts
|

N 8322 gas plasma inactivates influenza virus mediated by oxidative stress

Abstract: Here we show that N₂ gas plasma, produced by applying a short high-voltage pulse using a static induction (SI) thyristor power supply inactivates influenza virus. N₂ gas plasma treatment of influenza A and B viruses induced the degradation of viral proteins, including nucleoprotein, hemagglutinin, and neuraminidase. The injury of viral RNA genome and the inactivation of hemagglutination were also observed after N₂ gas plasma treatment. These changes were possibly due to changes in the viral envelope, because m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…However, the mechanisms of action of gas plasma on microorganisms remain to be elucidated. Previous studies have demonstrated that treatment of microorganisms with nitrogen gas plasma may induce changes in their lipids (5), proteins (7) and carbohydrates (8). These findings suggest that the changes induced by sterilizing factors produced during the generation of nitrogen gas plasma may contribute to the inactivation of microorganisms.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the mechanisms of action of gas plasma on microorganisms remain to be elucidated. Previous studies have demonstrated that treatment of microorganisms with nitrogen gas plasma may induce changes in their lipids (5), proteins (7) and carbohydrates (8). These findings suggest that the changes induced by sterilizing factors produced during the generation of nitrogen gas plasma may contribute to the inactivation of microorganisms.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, a nitrogen gas plasma instrument (BLP-TES), which generates nitrogen gas plasma using a fast high-voltage pulse from a static induction (SI) thyristor power supply was developed (5)(6)(7)(8)(9)(10)(11). Our previous studies (5)(6)(7)(8)(9)(10)(11) have demonstrated that nitrogen gas plasma can be utilized to inactivate various microorganisms. However, the mechanisms of action of gas plasma on microorganisms remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The determination wavelength was 200-650 nm, grating was 600 lines/mm, entrance slit width was 10 μm, exposure time was 100 ms and analyses were repeated 5 times. Production of one type of ROS, H 2 O 2 , has been reported by nitrogen gas plasma sterilization [16][17][18] , so we measured H 2 O 2 by using a chemical indicator (CI). The CI for H 2 O 2 analysis was from Quantofix Peroxide 25 (MACHEREY-NAGEL Ltd.) and the analysis range was 0-25 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial spores, vegetative bacteria, and viruses are all inactivated by the nitrogen gas plasma (Sakudo et al 2014; Maeda et al 2015). Several factors contribute to the thermal and non-thermal mechanism of inactivation, such as heat, ultraviolet (UV) radiation, and reactive chemical species generated during operation of the nitrogen gas plasma device.…”
Section: Introductionmentioning
confidence: 99%